Titanatos de alcalinos terrosos : a ordem associada à desordem - Moreira, Mário Lúcio (2010)
The microwave-assisted hydrothermal method was implemented in the synthesis of alkaline earth titanates under ABO3 stoichiometric known as perovskites, being efficient and innovative. For that, OH- groups played an important role since the coprecipitation of hydroxides to the dehydration of oxides for the formation of barium, calcium and strontium titanate at temperatures of 140 ° C with times from 10 to 160 min under 2.5 bar self-generated. During the dehydration / crystallization process of the hydrogen atoms may remain bound to oxygen causing a redistribution of local charges in the crystal lattice in order to stabilize it like a whole. This effect leads to the network polarizations, generated by small atomic displacements as microstructural distortions and casual vacancies of cations observed for BTO and STO, besides changes in dihedral angles for CTO. These polarizations will be able to cause the appearance or extinction of Raman vibrational modes without a drastic change on the phase symmetry of the materials. In the case of STO, fist order vibrational modes were detected in its cubic structure, for the BTO all observed vibrations correspond to the tetragonal phase and the CTO has an orthorhombic-orthorhombic transition related to the displacements of their vibrational modes. These changes of polarization for systems under study were also obtained from the simulation of Raman spectra, confirming and supporting the experimental results for each system. Thus the trapping of the hydrogen element is linked to local distortions through the formation of complexes clusters, mainly related to the atom network forming in its octahedral site. The formation of these clusters leads to the redistribution of the electronic states as a whole near the valence band and conduction band states by the hybridization of oxygen 2p and titanium 3d respectively. 13 This effect can be detected by absorption spectra of X-rays on the edge of the element titanium, and confirmed by "ab initio" simulations. Soon, new states near the bands may arise or be moved into the gap. In this case, such electronic states act as charge trapping centers, resulting after a specific excitation in the electron-hole pairs within the unstable band gap. Therefore, the different excitations employed in 350 and 415 nm allow us to produce different luminescent emission of individual system when the radioactive decay of these pairs. Thus, there was an intensification and / or disappearance of bands as a function of excitation applied. The CTO compound is the more efficient light emitting tooth the three materials. Thus the perovskites have become attractive materials with hybrid properties which make them even more attractive compounds for scientific research.